2021
DOI: 10.4081/ejtm.2021.9360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in kinesiostabilogram parameters and movement speed of stroke patients while increasing their physical activity due to the use of biofeedback method

Abstract: Balance disorders are complications of stroke survivors. Aim of this study was the establish effectiveness of the biofeedback approach. In this intervention study 245 patients with early diagnosis of acute disturbance of cerebral circulation (ADCC) were examined. Patients able to move independently were treated by standard conservative ADCC therapy on an outpatient approach, but they continued to have problems with coordination of movement in upright position. Then they were submitted to an increasing physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In most cases, stroke survivors may depend on their caregivers to take care of them due to severe motor dysfunction and because of their significantly limited self-care ability and social participation skills 4 8 9. When it comes to stroke, the high cost of healthcare is partly due to the increasing demand of dependence 5 10. In the past decade, the annual hospitalisation costs of stroke survivors have continued to increase rapidly, with an average rise of nearly 38% annually 5 6 11.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, stroke survivors may depend on their caregivers to take care of them due to severe motor dysfunction and because of their significantly limited self-care ability and social participation skills 4 8 9. When it comes to stroke, the high cost of healthcare is partly due to the increasing demand of dependence 5 10. In the past decade, the annual hospitalisation costs of stroke survivors have continued to increase rapidly, with an average rise of nearly 38% annually 5 6 11.…”
Section: Introductionmentioning
confidence: 99%
“…Task-oriented training (TOT) has been increasingly reported in recent years, and most researchers believe that compared with other methods, TOT is more effective in the treatment of stroke 9 16–19. It has been reported that TOT can accelerate the overall recovery process of stroke survivors, and participants who had an acute, subacute and chronic stroke can benefit from it 10 20 21. Both the USA and Canada have recommended TOT with a high level of evidence in their stroke treatment guidelines published in recent years 11 22 23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation